1995
DOI: 10.1002/jcb.240590213
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional insulin‐like growth factor‐II/mannose‐6‐phosphate receptors in isolated bone cells

Abstract: The role of the IGF-II/cation independent mannose-6-phosphate (IGF-II/M6P) receptor in the transduction of cellular effects evoked by IGF-II has been extensively debated in the literature. Many reports suggest that IGF-II transduces its effects through the IGF-I receptor, while others show that IGF-II utilizes the type II receptor to affect cellular activity. This study 1) verifies the presence of the IGF-II/M6P receptor in rat calvarial osteoblasts, and 2) evaluates the ability of the receptor to initiate int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Isolated osteoblasts were prepared from neonatal rat calvaria as previously described. (18) Biopanning procedure Two micrograms of TRAP in 0.1 M of sodium bicarbonate (pH 8.6) was used to coat microtiter plates for 16 h at 4°C. The wells were blocked for 1 h at 37°C with phosphate-buffered saline (PBS) containing 1% [wt/vol] bovine serum albumin (BSA).…”
Section: Methodsmentioning
confidence: 99%
“…Isolated osteoblasts were prepared from neonatal rat calvaria as previously described. (18) Biopanning procedure Two micrograms of TRAP in 0.1 M of sodium bicarbonate (pH 8.6) was used to coat microtiter plates for 16 h at 4°C. The wells were blocked for 1 h at 37°C with phosphate-buffered saline (PBS) containing 1% [wt/vol] bovine serum albumin (BSA).…”
Section: Methodsmentioning
confidence: 99%
“…We isolated rat calvarial primary osteoblast (ROB) cells as described. (14) ROB cells were cultured in low glucose Dulbecco's Modified Eagle Medium (DMEM) (Invitrogen, Grand Island, NY, USA) with 5% fetal bovine serum (FBS) (Sigma-Aldrich, St. Louis, MO, USA) and 50 mg/mL ascorbic acid. For osteoblast differentiation assays, a final concentration of 10 mM b-glycerophosphate (BGP) was also added to the media.…”
Section: Cell Culturementioning
confidence: 99%
“…Because the IGF-II/M6P receptor lacks intrinsic catalytic activity, most of the biological effects of IGF-II have been attributed either to the IGF-I receptor [13] or IR-A [8]. Nonetheless, a number of studies over the years have suggested that certain biological effects of IGF-II are being triggered directly via the IGF-II/M6P receptor, including calcium influx in mouse embryo fibroblasts [104] and rat calvarial osteoblasts [105], increased protein phosphorylation [106] and alkalinization in proximal renal tubule cells [107], stimulation of Na + /H + exchange and inositol trisphosphate production in canine kidney cells [108], increased amino acid uptake in muscle cells [109], increased glycogen synthesis in hepatoma cells [110], proteoglycan synthesis in human chondrosarcoma cells [111], calcium mobilization in rabbit articular chondrocytes [112], cell motility in rhabdomyosarcoma cells [113, 114], aromatase activity in placenta cytotrophoblasts [115], migration of human extravillous trophoblasts [116], insulin exocytosis by pancreatic β cells [117], and regulation of endogenous acetylcholine and GABA release from the adult rat brain [118, 119]. …”
Section: Functions Of the Igf-ii/m6p Receptormentioning
confidence: 99%